Design, synthesis, crystal structure, in vitro cytotoxicity evaluation, density functional theory calculations and docking studies of 2-(benzamido) benzohydrazide derivatives as potent AChE and BChE inhibitors. Issue 1 (24th December 2021) - Kausar, Naghmana; Murtaza, Shahzad; Arshad, Muhammad Nadeem; Zaib Saleem, Rahman Shah; Asiri, Abdullah M.; Kausar, Samia; Altaf, Ataf Ali; Tatheer, Adina; Elnaggar, Ashraf Y.; El-Bahy, Salah M.
Abstract : 2-(Benzamido) benzohydrazide derivatives: synthesis from methyl anthranilate and application as potent anti-Alzheimer's agents. Abstract : A series of hydrazone derivatives of 2-(benzamido) benzohydrazide was designed, synthesized, and characterized utilizing FTIR, NMR and UV spectroscopic techniques along with mass spectrometry. Compound 10 was also characterized through X-ray crystallography. These synthesized compounds were assessed for their potential as anti-Alzheimer's agents by checking their AChE and BChE inhibition properties by in vitro analysis. The synthesized derivatives were also evaluated for their antioxidant potential along with cytotoxicity studies. The results clearly indicated that dual inhibition of both the enzymes acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) was achieved by most of the compounds (03–13 ), showing varying IC50 values. Remarkably, compound 06 (IC50 = 0.09 ± 0.05 for AChE and 0.14 ± 0.05 for BChE) and compound 13 (IC50 = 0.11 ± 0.03 for AChE and 0.10 ± 0.06 for BChE) from the series showed IC50 values comparable to the standard donepezil (IC50 = 0.10 ± 0.02 for AChE and 0.14 ± 0.03 for BChE). Moreover, the derivative 11 also exhibited selective inhibition against BChE with IC50 = 0.12 ± 0.09. Meanwhile, compounds 04 and 10 exhibited good anti-oxidant activities, showing % scavenging of 95.06% and 82.55%, respectively. Cytotoxicity studies showed that the synthesized compounds showed cell viability greater than 80%; thus, these compounds can be safely used as drugs. DFT and molecular docking studies also supported the experimental findings.